GM food crops ? no evidence that they bring benefits - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Miriam Mayet is an environmental lawyer from South Africa working with NGOs on environmental issues. She is very concerned about modern biotechnology, specifically genetic engineering and GM feed crops